The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fneur.2018.00197
|View full text |Cite
|
Sign up to set email alerts
|

Olivocochlear Efferents in Animals and Humans: From Anatomy to Clinical Relevance

Abstract: Olivocochlear efferents allow the central auditory system to adjust the functioning of the inner ear during active and passive listening. While many aspects of efferent anatomy, physiology and function are well established, others remain controversial. This article reviews the current knowledge on olivocochlear efferents, with emphasis on human medial efferents. The review covers (1) the anatomy and physiology of olivocochlear efferents in animals; (2) the methods used for investigating this auditory feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 200 publications
(296 reference statements)
8
73
0
5
Order By: Relevance
“…Specifically, medial efferent innervation provides inhibitory input to the OHCs and, thereby, regulates the cochlear amplifier. In this way, medial efferent innervation is believed to improve signal transduction, enhance signal detection, and protect the cochlea from noise‐induced injury (reviewed in both Guinan, ; Lopez‐Poveda, ). Thus, our findings of reduced medial efferent innervation density are consistent with previous reports of reduced cochlear tuning in a related mole rat species, F. anselli (Kössl et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, medial efferent innervation provides inhibitory input to the OHCs and, thereby, regulates the cochlear amplifier. In this way, medial efferent innervation is believed to improve signal transduction, enhance signal detection, and protect the cochlea from noise‐induced injury (reviewed in both Guinan, ; Lopez‐Poveda, ). Thus, our findings of reduced medial efferent innervation density are consistent with previous reports of reduced cochlear tuning in a related mole rat species, F. anselli (Kössl et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Our study shows that intramodal top-down attention may modulate the processing of predictable spectral input in the peripheral auditory system, thereby adding support to current debate on the sensitivity of the human auditory peripheral system to top-down modulation (e.g., Beim et al, 2018;Lopez-Poveda, 2018). Our observations further indicate that predictability may affect auditory processing in the peripheral auditory system.…”
Section: Resultssupporting
confidence: 77%
“…Efferent MOC signals may alter the amplitudes and phases of the two DPOAE components (primaries) by different amounts, which can result in either positive or negative DPOAE-level changes depending on the specific primary frequencies (Guinan, 2006)an ambiguity that might explain why some previous DPOAE studies observed opposite effects of auditory attention (Smith et al, 2012;Srinivasan et al, 2012Srinivasan et al, , 2014Wittekindt et al, 2014). Future studies may disambiguate the direction of peripheral predictability effects by measuring, e.g., stimulus-frequency OAEs (SFOAEs), which require only a single test frequency but otherwise more sophisticated methods (Guinan, 2006;Lopez-Poveda, 2018). In sum, our DPOAE results suggest that OHCs may be sensitive to auditory predictability when the listener is paying top-down attention to the acoustic input.…”
Section: Predictability-induced Changes In Auditory Peripheral Responsesmentioning
confidence: 99%
See 2 more Smart Citations